(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the prevention of symptomatic arterial hypertension. Symptomatic hypertension is a secondary increase in blood pressure that occurs as a result of other diseases, with its main causes including diseases of the kidneys, endocrine system, and cardiovascular system. The article analyzes methods of prevention, early diagnosis, and treatment of these diseases. As preventive measures, the importance of adhering to a healthy lifestyle, reducing stress, rational nutrition, and regular medical monitoring is emphasized. The results of the study show that a comprehensive approach is necessary to prevent symptomatic arterial hypertension and reduce its negative consequences.